Dominant environmental factors influencing soil metal concentrations of Poyang Lake wetland, China: Soil property, topography, plant species and wetland type - Xu, Jinying; Wang, Xiaolong; Wang, Jingbo; Xu, Ligang; Zheng, Xiongwei; Zhang, Yuanpei; Hu, Chunhua (Catena (Giessen), 2021)
•TN, TP, NO3−-N, PO43−-P and TOC played a dominant role in soil metal concentrations.•Lower elevations favored soil metal accumulation.•Artemisia and Phalaris benefited some metals accumulated in wetland soil.•Wetland type with low flat terrain benefited wetland soil metal accumulation. Although an important sink for contaminants including metals, wetland soils can release metals and thus cause a secondary pollution when environmental condition changes. Metals in wetland soils are influenced by a variety of environmental factors, including soil property, topography, wetland type, and plant species. However, the degree of importance of these environmental factors to wetland soil metals has not yet been clearly explained. In this study, the effect of these environmental factors on soil metal concentrations (i.e., Cr, Ni, Cu, Zn, As, Cd, and Pb) was explored in Poyang Lake wetland. Correlation, redundancy, and variance decomposition analyses were employed. The results indicate that the concentrations of Cu, Pb, Cd, Cr, and Zn were higher than their background values. Statistical analysis showed that all environmental factors explained 55.90% of the total variance (either p < 0.01 or p < 0.05). Soil properties, mainly TN, TP, NO3−-N, PO43−-P, and TOC played a dominant role on soil metal concentrations, which explained 27.91% of the total variance, followed by wetland type and topography, which explained 5.55% and 3.19% of the total variance, respectively. Soil nutrients significantly promoted metal aggregation in soil (p < 0.01 or p < 0.05). Lower elevations were favorable for soil metal accumulation (p < 0.05). Wetland type indirectly influenced soil metal concentrations, where wetlands with low flat terrain promoted soil nutrients accumulation, thus enhancing metal accumulation by soils. Plant species explained 6.72% of the variance, and Artemisia and Phalaris were positively correlated with specific metals in soils. This study provides a theoretical basis for retaining healthy wetland ecosystems.